Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.4049/jimmunol.0803829
|View full text |Cite
|
Sign up to set email alerts
|

Effector/Memory but Not Naive Regulatory T Cells Are Responsible for the Loss of Concomitant Tumor Immunity

Abstract: The phenomenon of concomitant tumor immunity involves a tumor-bearing host rejecting another similar tumor at a distant site and suggests the existence of tumor-specific immunity. Loss of this immunity may contribute to tumor metastasis. However, mechanisms underlying the loss of concomitant immunity are largely unknown. We set up a concomitant tumor immunity model in which this immunity is gradually lost as the primary tumor progresses. We found that CD8+ T cells, especially tumor-infiltrating CD8+ T cells, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 48 publications
1
52
0
Order By: Relevance
“…These CD103 + Tregs are more potent in suppressing harmful inflammatory reactions compared with CD103 2 Tregs in different mouse models of autoimmune diseases and Leishmania infection (3,4,6). In contrast, we also reported that CD103 + Tregs were potent suppressors of anti-tumor immune responses in tumor-bearing mice (8). Recent studies have also shown that CD103 is a hallmark of tumor-infiltrating Tregs in TGF-bsecreting tumor (9).…”
Section: R Egulatory T Cells (Tregs) Play An Important Role In the Mamentioning
confidence: 63%
See 2 more Smart Citations
“…These CD103 + Tregs are more potent in suppressing harmful inflammatory reactions compared with CD103 2 Tregs in different mouse models of autoimmune diseases and Leishmania infection (3,4,6). In contrast, we also reported that CD103 + Tregs were potent suppressors of anti-tumor immune responses in tumor-bearing mice (8). Recent studies have also shown that CD103 is a hallmark of tumor-infiltrating Tregs in TGF-bsecreting tumor (9).…”
Section: R Egulatory T Cells (Tregs) Play An Important Role In the Mamentioning
confidence: 63%
“…It has been shown that chemokine receptors CCR3, CCR4, and CCR5 could mediate trafficking of Tregs to tumors (8,(14)(15)(16). We next examined the expression of these chemokine receptors on CD103 + Tregs in the spleen and tumors of mice bearing CT26 tumors.…”
Section: Tregs In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 In human studies, Sakaguchi's group demonstrated CD45RA ¡ Foxp3 high Treg cells as effector Treg cells which are increased in patients with cancer. 1,6 We have also shown these CD45RA ¡ Foxp3 high effector Treg cells were highly suppressive, accumulated in tumor tissues and correlated with disease progression in patients with CRC.…”
Section: Introductionmentioning
confidence: 99%
“…This effect is lost during tumor progression as shown in our previous studies. 4 We investigated whether this loss of concomitant tumor immunity is tumor specific or not. We chose CT26 cells and BNL cells for these studies.…”
Section: Introductionmentioning
confidence: 99%